Metody klasyfikacji dla danych symbolicznych - symulacja porównawcza - Dudek, Andrzej (Classification Methods for Symbolic Data - Comparative Simulation, 2007)
The article presents typical cluster analysis study for symbolic data, main dissimilarity measures for symbolic data, selection of clustering methods for symbolic data and determination of the number of classes described. Nine clustering methods: Ward, single link, complete link, average, Mcquitty, median, centroid, partitioning around medoids and dynamic clustering for symbolic objects (SCLUST) are compared on 105 sets of symbolic data and some recommendations regarding cluster analysis of symbolic data are proposed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 19-26